Application Four Type of Ameliorant to Increase Cucumber - Wicaksono, Aditya Pandu (PLANTROPICA: Journal of Agricultural Science, 2016)
Application of ameliorant is one of solution to improve saline soil. The purpose of this research were to get the most effective land ameliorant for growth and yield of Cucumber (Cucumis sativus L.) varieties Metavy and Monza in saline land. This research was conducted from May to October 2016. It located at Sidomukti village, Brondong district, Lamongan that has saline lands with EC value Â± 4.8 dS m-1.